Movement and nutrition in COVID-19 - Lange, K. W.; Nakamura, Y. (Movement and Nutrition in Health and Disease, 2020)
Movement and nutrition appear to play important roles in the management of the novel coronavirus disease 2019 (COVID-19). Moderate physical exercise has a positive impact on immune function, can counteract age-associated immune deficiency and is capable of reducing the incidence of respiratory diseases. Exercise can also mitigate the negative effects of home confinement due to quarantine and of other preventive measures, which may lead to an increase in sedentary behaviours and a reduction in physical activity. Regular physical exercise may have benefits in regard to infection risk, mental problems, such as anxiety and depression, and maintenance of body weight as well as the prevention and management of chronic disease. Since evidence evaluating dietary supplementation in COVID-19 is lacking, a reliance on supplements to prevent or treat COVID-19 would be premature. A balanced diet containing sufficient amounts of macronutrients and diverse micronutrients is required for an optimally functioning immune system. High-energy diets and obesity are major risk factors for a more severe course of COVID-19. Population-wide body weight control is therefore an important preventive measure. Other lifestyle-related factors, such as reducing smoking rates and limiting alcohol intake, are also important in decreasing disruptive effects on immune functioning and improving ability to overcome infection.